Enhancing Educational Quality: Insights from Permanent Teachers in Nepalese Public Secondary Schools - Niure, Dhruba Prasad; Sapkota, Madhabi (Interdisciplinary Research in Education, 2024)
This article explores various approaches to enhancing the quality of education in Nepalese public schools, aiming at maximizing the educational access and success for all. Using an interpretive paradigm followed by narrative research design, the article investigates the perspectives of eight permanently employed secondary-level teachers who, despite working in public schools, chose private schools for their children’s education. Open-ended interviews were conducted to investigate their perspectives on improving public school education in Nepal. Triangulation, member checking, and thick description were used to ensure the credibility and authenticity of information collected from the samples. Study findings revealed that dynamic leadership, infrastructure enhancement, institutionalizing school as a zone of peace, regular monitoring, community involvement in schools’ activities, intensive teacher training for continuous professional development, and home-school collaboration for effective learning play crucial role in determining educational quality in public schools in Nepal. Thus, this article provides a valuable insight into various factors that need to be addressed to improve overall quality of public education in Nepal.